Rola Wojsk Obrony Terytorialnejw zarządzaniu kryzysowym w czasie pandemii COVID-19 = The role of the Territorial Defense Forcesin crisis management during the COVID-19 pandemic - Dalecka-Zaborowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to show the involvement of territorial troops in counteracting the threats resulting from the COVID-19 pandemic. The author, based on a review of the legal and organizational basis for creating the Territorial Defense Forces, opinions of experts and military researchers, and a review of source materials of the Territorial Defense Forces, attempted to analyze the role and capacity building of territorial forces during the pandemic crisis.
Keywords: zarządzanie kryzysowe; Wojska Obrony Terytorialnej; pandemia; COVID-19; crisis management; Territorial Defense Forces; pandemic